Histology predicts cirrhotic evolution of post transplant hepatitis C. Issue 5 (1st May 2002) - Guido, M; Fagiuoli, S; Tessari, G; Burra, P; Leandro, G; Boccagni, P; Cillo, U; Naccarato, R; Rugge, M
Abstract : Background: Hepatitis C recurring after orthotopic liver transplantation varies in severity and some patients rapidly develop fully established liver cirrhosis. Neither clinical nor biological markers of such rapid cirrhotic evolution are available. Aim: To assess the value of histology in identifying patients who will develop cirrhosis shortly after liver transplantation. Patients and methods: Only cases of recurrent hepatitis C diagnosed by both hepatitis C virus-RNA positive serum and liver changes consistent with hepatitis, with no other causes of allograft injury, were considered. A total of 128 liver biopsies were scored from 29 consecutive patients with a mean follow up of 48 (13.97) months. The histological activity index was evaluated according to Ishak et al . The time of the first histological diagnosis of recurrent hepatitis C in the absence of rejection was defined as time of histological recurrence (RHC-T). Results: First histological diagnosis of recurrent hepatitis with no features of rejection was obtained at the six month biopsy in 23 of 29 cases. By the end of follow up, nine patients had developed cirrhosis (mean follow up 38 (14.39) months (range 18–60)). The remainder (mean follow up 46 (13.40) months (24–72)) showed a spectrum of fibrosis but no cirrhosis. Severe necroinflammatory lesions at RHC-T significantly correlated with rapid development of cirrhosis. At the RHC-T biopsy, only cases evolving into cirrhosis showed confluent necrosis. The median value of the histological activity index was 11 (mean 11.11 (1.76) (range 9–14)) in patients who developed cirrhosis and four (mean 4 (1.78) (range 1–8)) in the others (p<0.0001). A histological activity index ≥9 was associated with rapid development of cirrhosis in 100% of cases. Conclusions: After liver transplantation, the histological activity of recurrent hepatitis C predicts the risk of development of cirrhosis. By adopting Ishak's scoring system, a histological activity index ≥9 was 100% sensitive/specific in identifying subjects who rapidly developed cirrhosis.